Efficacy of a single measurement of plasma anti-Müllerian hormone concentration for ovum pick-up donor selection of Japanese Black heifers in herd breeding programs - Yasuo FUSHIMI; Danielle MONNIAUX; Mitsuhiro TAKAGI (The Journal of Reproduction and Development, 2019)
In this study, we evaluated the efficiency of a single measurement of plasma anti-Müllerian hormone (AMH) concentration in heifers in determining the number of oocytes recoverable by ovum pick-up (OPU), and compared AMH concentrations among sister heifers from the same parents. For this, blood samples from 50 embryo-transfer-derived female Japanese Black (JB) heifers (mean: 8.7 age in months) were collected and plasma AMH concentration was measured. At 13–15 months of age, both the number of follicles (2–9 mm) and the number of collected oocytes after OPU were counted and compared. Results indicated that the heifers with the highest AMH concentration had the highest number of follicles in their ovaries and gave the highest number of collected oocytes with OPU, thereby indicating that a single measurement of plasma AMH concentration is informative for the selection of OPU-donor heifers in herd breeding programs. The practice of performing a single AMH measurement may accelerate the intensive breeding of JB herds.